2021
DOI: 10.1016/j.tig.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the DNA methylation landscape of cancer

Abstract: DNA methylation is a chemical modification that defines cell type and lineage through the control of gene expression and genome stability. Disruption of DNA methylation control mechanisms causes a variety of diseases, including cancer. Cancer cells are characterized by aberrant DNA methylation (i.e., genome-wide hypomethylation and site-specific hypermethylation), mainly targeting CpG islands in gene expression regulatory elements. In particular, the early findings that a variety of tumor suppressor genes (TSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
257
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(330 citation statements)
references
References 183 publications
4
257
0
5
Order By: Relevance
“…Cancer cells are characterized by aberrant DNA methylation (e.g., genome-wide hypomethylation and site-speci c hypermethylation), mainly targeting CpG islands in gene expression regulatory elements. In particular, the early ndings that a variety of tumor suppressor genes are targets of DNA hypermethylation in cancer led to the proposal of a model in which aberrant DNA methylation promotes cellular oncogenesis through TSGs silencing (Nishiyama and Nakanishi, 2021). The present study showed that DNA methylation of GDF15 was downregulated in most common cancers, which is consistent with the upregulation of the GDF15 expression.…”
Section: Discussionsupporting
confidence: 80%
“…Cancer cells are characterized by aberrant DNA methylation (e.g., genome-wide hypomethylation and site-speci c hypermethylation), mainly targeting CpG islands in gene expression regulatory elements. In particular, the early ndings that a variety of tumor suppressor genes are targets of DNA hypermethylation in cancer led to the proposal of a model in which aberrant DNA methylation promotes cellular oncogenesis through TSGs silencing (Nishiyama and Nakanishi, 2021). The present study showed that DNA methylation of GDF15 was downregulated in most common cancers, which is consistent with the upregulation of the GDF15 expression.…”
Section: Discussionsupporting
confidence: 80%
“…In mammals, three active DNMTs are found and designated as DNMT1, DNMT3a, and DNMT3b. As there are many excellent reviews on these enzymes and DNA methylation, we refer our readers to a few of these comprehensive articles [ 23 – 25 ].…”
Section: Overview Of Epigenetic Pathways the Enzymes And Inhibitorsmentioning
confidence: 99%
“…In most cancers, local hypermethylation occurs in 5–10% of the CpG islands in promoter regions, leading to silencing of important tumor suppressor genes [ 64 ]. For example, genes encoding the retinoblastoma tumor suppressor ( RB1 ), cell cycle inhibitors p16 INK4a ( CDKN2A ) and p15 INK4a ( CDKN2B ), mismatch repair factor MLH1 , inhibitory molecules for cancer invasion and metastasis such as E-cadherin ( CDH1 ) and H-cadherin ( CDH13 ), the apoptosis signal regulator DAPK1 , and various transcription factors involved in tumor suppression are negatively regulated by DNA hypermethylation in cancer [ 65 ]. Among apoptosis-inducers, epigenetic silencing of BIM or PUMA has been reported in several cancers, including renal cell carcinoma and Burkitt lymphoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%